Microenvironment and drug resistance in acute myeloid leukemia: Do we know enough?. Issue 9 (24th December 2021) - Ganesan, Saravanan; Mathews, Vikram; Vyas, Neha
Abstract: Acute myeloid leukemia (AMLs), as the name suggests, often develop suddenly and are very progressive forms of cancer. Unlike in acute promyelocytic leukemia, a subtype of AML, the outcomes in most other AMLs remain poor. This is mainly attributed to the acquired drug resistance and lack of targeted therapy. Different studies across laboratories suggest that the cellular mechanisms to impart therapy resistance are often very dynamic and should be identified in a context‐specific manner. Our review highlights the progress made so far in identifying the different cellular mechanisms of mutation‐independent therapy resistance in AML. It reiterates that for more effective outcomes cancer therapies should acquire a more tailored approach where the protective interactions between the cancer cells and their niches are identified and targeted. Abstract :